Finland - Morison, Samuel Eliot, 1887-1976 (1918)
This is a memorandum containing concise analysis of Finland, with particular emphasis on political events and conditions in 1918. Includes opinion as to the possible outcomes of peace with Germany and the role of Finland's potential annexation to Sweden, Germany, or Russia in a negotiated peace.